Coronal tibial slope is associated with accelerated knee osteoarthritis: data from the Osteoarthritis Initiative. - Driban, Jeffrey B.; Stout, Alina C.; Duryea, Jeffrey.; Lo, Grace H.; Harvey, William F.; Price, Lori Lyn.; Ward, Robert J.; Eaton, Charles B.; Barbe, Mary F.; Lu, Bing.; McAlindon, Timothy E. (2016)
Background: Accelerated knee osteoarthritis may be a unique subset of knee osteoarthritis, which is associated with greater knee pain and disability. Identifying risk factors for accelerated knee osteoarthritis is vital to recognizing people who will develop accelerated knee osteoarthritis and initiating early interventions. The geometry of an articular surface (e.g., coronal tibial slope), which is a determinant of altered joint biomechanics, may be an important risk factor for incident accelerated knee osteoarthritis. We aimed to determine if baseline coronal tibial slope is associated with incident accelerated knee osteoarthritis or common knee osteoarthritis.; Keywords: Knee, Osteoarthritis, Bone, Alignment, Radiography.; Springer Open.